Explanation of Local Elections in Iran from the Perspective of the Geopolitics of Gender (Case Study: Urban and Rural Council Elections in Fars Province) - nayereh akhavan; Narjessadat hossainy nasrabady (تحقیقات کاربردی علوم جغرافیایی)
Gender distribution in the centers of power and the level of participation in elections from a gender perspective are among the ambiguous issues that show the composition and quality of power structures in political-spatial units. From a geopolitical perspective, how power is distributed through representation and political participation through elections reflects the presence or absence of gender justice in power structures. Given the high geopolitical weight of women in the Iranian population pyramid, the present study has reviewed the city and village council elections in Fars province from a geopolitical perspective of gender. For this purpose, by using descriptive and survey methods and by examining different statistics and data in the three rounds of city and village council elections in Fars province, the gender distribution of the elected representatives in these three rounds has been investigated. Is. The results showed that in the first round of urban and rural elections in Fars province, men held 90% of the seats. In the second round, this ratio reaches 80%, and in fact, there is a relative improvement in the gender distribution of representatives. In the third round, however, the sinusoidal trend reverses to the first round so that the gender weight of the representation remains established in the masculine structure.